Fire-Induced Smoke Movement and Control - Fan, Chuangang; Qi, Dahai (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Fire-induced smoke influences the safe evacuation of occupants and firefighters' ability to extinguish a fire. About 80% of deaths in fires were caused by toxic smoke, according to statistics. Hence, how to control smoke is of great importance in order to reduce fire hazards. In this Special Issue, the scope was to gather original, fundamental and applied research concerning experimental, theoretical, computational and case studies that contribute towards the understanding of fire-induced smoke.